KEPEMIMPINAN VISIONER DAN NILAI-NILAI STRATEGIK: MODEL PENGUATAN REPUTASI INSTITUSI PENDIDIKAN PADA ERA TRANSFORMASI DIGITAL - Evi Muliani; Efa Herlina Batubara; Eva Rosdiana Br Sitepu; Catur Prida Retnivia; Pratisa Martha Sari; Widyatmike Gede Mulawarman; Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of visionary leadership on institutional reputation in higher education, with strategic values and digital capability serving as mediating variables. A quantitative approach was applied using SEM-PLS based on 280 simulated (dummy) data points, constructed realistically to follow common empirical patterns in educational management research. The results indicate that visionary leadership significantly influences strategic values (β = 0.649) and digital capability (β = 0.605), yet it does not have a significant direct effect on institutional reputation (p > 0.05). Institutional reputation is strongly influenced by strategic values (β = 0.514) and digital capability (β = 0.332). Moreover, digital capability significantly mediates the relationship between visionary leadership and institutional reputation. The model demonstrates strong predictive power with an R² value of 0.693. These findings suggest that the reputation of educational institutions in the digital era relies heavily on the implementation of strategic values and the effectiveness of digital capability development. The study recommends strengthening value-based management and accelerating digital transformation to improve institutional reputation.